Impacts of co-management on fish biodiversity and livelihoods of fishers of Baikka beel, Moulvibazar, Bangladesh - Kabeer, Fozlul; Hossain, Md Jamal; Paul, Subrato; Islam, Taufiqul (Journal of the Bangladesh Agricultural University, 2018)
Co-management plays a significant role in fisheries and natural resources management. In the case of fisheries, it has most often been taken to mean a sharing of responsibility for sustainable resource management between government and fishing communities. Baikka Beel, situated in Moulvibazar, Bangladesh has been identified and established as a wetland sanctuary by local community members in conjunction with the Management of Aquatic Ecosystem through Community Husbandry (MACH) project. In this study, the role of co-management institutions, including federations of resource user groups (FRUGs) and resource management organizations (RMOs) were investigated on sustainable wetland resource management and fish production and biodiversity in Baikka Beel. Study results shown that the knowledge and attitudes of MACH fishers towards sustainable resource management were positive and optimistic than non-MACH fishers; MACH fishers were involved with AIGAs. The results from independent samples t-test showed that the income of MACH group from fishing was significantly lower than the income of non-MACH group while income from AIGAs of MACH group was significantly higher than the income of non-MACH group. Fishing rights of both MACH and non-MACH fishers are not well established due to current leasing system. Both production and biodiversity of fish has been improved due to community-based sustainable management of Baikka Beel. J. Bangladesh Agril. Univ. 16(2): 328-336, August 2018